An overview of current techniques for ocular toxicity testing. - Ahearne, Mark (My University, 2015)
Abstract Given the hazardous nature of many materials and substances, ocular toxicity testing is required to evaluate the dangers associated with these substances after their exposure to the eye. Historically, animal tests such as the Draize test were exclusively used to determine the level of ocular toxicity by applying a test substance to a live rabbit’s eye and evaluating the biological response. In recent years, legislation in many developed countries has been introduced to try to reduce animal testing and promote alternative techniques. These techniques include ex vivo tests on deceased animal tissue, computational models that use algorithms to apply existing data to new chemicals and in vitro assays based on two dimensional (2D) and three dimensional (3D) cell culture models. Here we provide a comprehensive overview of the latest advances in ocular toxicity testing techniques, and discuss the regulatory framework used to evaluate their suitability.
PUBLISHED
Keywords: ocular toxicity testing; ocular toxicity testing; Next Generation Medical Devices